2021
DOI: 10.1002/wmh3.401
|View full text |Cite
|
Sign up to set email alerts
|

A Call for the World Health Organization to Create International Classification of Disease Diagnostic Codes for Post‐Intensive Care Syndrome in the Age of COVID‐19

Abstract: Post‐intensive care syndrome (PICS), a condition found in survivors of critical illness, is characterized by persistent physical, cognitive, and psychological sequelae that impact the quality of life after discharge from an intensive care unit (ICU). At present, there are no International Classification of Disease (ICD) billing codes for this condition. Without financial alignment, clinicians cannot diagnose PICS, hindering tracking of its prevalence and impeding policy development for this condition. Clinicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…A definition founded in the umbrella term postulated by the Society of Critical Care Medicine in 2012 [2] and applied in recent publications in absence of alternative diagnostic tools [33,52,53]. As no diagnostic tools for PICS exist at this moment [54], the population in our study cannot be formally identified as having PICS, although our secondary outcome data show that participants experienced impairments in physical, psychological, and/or cognitive domains. Clinical tools are needed to identify the presence of PICS and the extent of PICS-related disability, and although recently the development and validation of some tools have been investigated, further studies are urgently needed for better definition and understanding of PICS [54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A definition founded in the umbrella term postulated by the Society of Critical Care Medicine in 2012 [2] and applied in recent publications in absence of alternative diagnostic tools [33,52,53]. As no diagnostic tools for PICS exist at this moment [54], the population in our study cannot be formally identified as having PICS, although our secondary outcome data show that participants experienced impairments in physical, psychological, and/or cognitive domains. Clinical tools are needed to identify the presence of PICS and the extent of PICS-related disability, and although recently the development and validation of some tools have been investigated, further studies are urgently needed for better definition and understanding of PICS [54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 91%
“…Clinical tools are needed to identify the presence of PICS and the extent of PICS-related disability, and although recently the development and validation of some tools have been investigated, further studies are urgently needed for better definition and understanding of PICS [54][55][56][57][58]. Working with the limitation of a not clearly defined population, we designed a patient-centered intervention embedded within an interdisciplinary collaborative network addressing the complex cluster of problems in patients with PICS conform recent recommendations [12,33,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When HRQOL was assessed in a case series of post-ICU COVID-19 cases, they all showed impairment when assessed with the use of the SF 36 at 3 months [135]. A call has already been made to the World Health Organization (WHO) to develop International Classification of Disease Diagnostic Codes for PICS in the "Age of COVID-19" [136]. Follow-ups of these patients in post-ICU clinics and in primary care are paramount and, in many cases, must be performed with virtual visits, and support of patients and families must be provided through the internet [137].…”
Section: Covid-19-related Picsmentioning
confidence: 99%
“…Therefore, follow-up of the critically ill patients who survived COVID-19 which is thought to have long-term effects on patients, should be systematically performed from this point of view by all aspects. Considering that PICS do not even have an International Classification of Disease Diagnostic (ICD) Code yet, it has been suggested that an ICD code should be created for PICS within the era of COVID-19 pandemic [47]. 3…”
Section: Discussionmentioning
confidence: 99%